Spontaneous Vertebral Artery Arteriovenous Fistula with Neurofibromatosis Type I and Its Management with Covered Stent - Diyora, Batuk; Purandare, Anup; Devani, Kavin; Palave, Prakash (Asian Journal of Neurosurgery, 2023)
Vertebro-vertebral fistulas (VVFs) are uncommon vascular pathology. It can be either primary (spontaneous) or secondary (iatrogenic or mechanical trauma). Spontaneous vertebral arteriovenous malformation is often associated with connective tissue disorders. Cases associated with neurofibromatosis type I (NF I) are even rarer. Management of VVF with covered stent is an emerging option for construction of vertebral artery. It not only preserves the flow of the parent artery but also has immediate exclusion of the fistula from the parent artery. A 30-year-old pregnant female patient presented with cervical bruit and left upper limb radiculopathy. She was a known case of NF I. Magnetic resonance imaging cervical spine revealed multiple flow voids compressing the cervical spinal cord and nerve roots. Digital subtraction angiography revealed a vertebral artery arteriovenous fistula. She underwent endovascular treatment in the form of a covered stent. Her clinical symptoms immediately improved. She was asymptomatic at the 1-year follow-up.
Keywords: spontaneous vertebral artery arteriovenous fistula; neurofibromatosis; endovascular treatment; covered stent; arteriovenous malformation